Neuroprotective effects of multifaceted hybrid agents targeting MAO, cholinesterase, iron and β‐amyloid in ageing and Alzheimer's disease - Weinreb, Orly (Br J Pharmacol, 2015)
Alzheimer's disease (AD) is accepted nowadays as a complex neurodegenerative disorder with multifaceted cerebral pathologies, including extracellular deposition of amyloid β peptide‐containing plaques, intracellular neurofibrillary tangles, progressive loss of cholinergic neurons, metal dyshomeostasis, mitochondrial dysfunction, neuroinflammation, glutamate excitoxicity, oxidative stress and increased MAO enzyme activity. This may explain why it is currently widely accepted that a more effective therapy for AD would result from the use of multifunctional drugs, which may affect more than one brain target involved in the disease pathology. The current review will discuss the potential benefits of novel multimodal neuroprotective, brain permeable drugs, recently developed by Youdim and collaborators, as a valuable therapeutic approach for AD treatment. The pharmacological and neuroprotective properties of these multitarget‐directed ligands, which target MAO enzymes, the cholinergic system, iron accumulation and amyloid β peptide generation/aggregation are described, with a special emphasis on their potential therapeutic value for ageing and AD‐associated cognitive functions. This review is conceived as a tribute to the broad neuropharmacology work of Professor Moussa Youdim, Professor Emeritus in the Faculty of Medicine and Director of Eve Topf Center of Excellence in Technion‐Israel Institute of Technology, and Chief Scientific Officer of ABITAL Pharma Pipeline Ltd., at the occasion of his 75th birthday. LINKED ARTICLES: This article is part of a themed section on Updating Neuropathology and Neuropharmacology of Monoaminergic Systems. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v173.13/issuetoc